Electrochemical exfoliation-streamline method for synthesis of nitrogen doped graphene - Olins, Roberts; Lesnicenoks, Peteris; Kleperis, Janis; Knoks, Ainars; Lukosevics, Ingars (Lithuanian Academy of Sciences Publishers, 2021)
Graphene was discovered in the early 21st century, but has already proven itself in many applications – energy, medicine, electronics, food and sports, and more. Functionalization of nanostructured carbon materials with both non-metallic and metallic atoms is possible in various ways, imparting enhanced or new properties to the starting material, even catalytic activity. A method of electrochemical exfoliation was used to obtain the graphene sheets and simultaneously functionalize them with nitrogen. To ensure N-doping the process is done in a NaN3 electrolyte solution which provides less quantity of oxygen groups that tend to block defect sites on the graphene, compared with such solvents as NaNO2. Two graphite electrodes are inserted into the electrolyte and a pulse power of 0–10V is applied. The solution containing the obtained material is filtered through a 0.1 µm filter and dried. The material is characterized using SEM, XRD and XPS. In the XPS characterization graphene oxide is used as a reference material.
The authors gratefully acknowledge financial support from the Latvian Council of Science, Project LZP FLPP No. LZP-2018/1 0194, and the Institute of Solid State Physics, University of Latvia that as the Center of Excellence has received funding from the European Union’s Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2026-2017-TeamingPhase2 under Grant Agreement No. 739508, Project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics; nitrogen-doped graphene; sodium azide; sodium nitrite; electrochemical exfoliation